2022
DOI: 10.21511/imfi.19(1).2022.15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fiscal and monetary policy on inflation in Vietnam

Abstract: High and sustainable growth of gross domestic product with stable inflation is one of the objectives of the most macroeconomic policies both in the world and in Vietnam. Therefore, price stability plays a vital role in assuring GDP growth. In order to stabilize prices, fiscal and monetary policies need to be appropriately managed. The aim of this study is to assess the impact of the monetary and fiscal policies on inflation in Vietnam during the period from 1997 to 2020. This study has applied the vector autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between economic growth and monetary policy, specifically the role of policy interest rates, was extensively examined by (Arintoko & Kadarwati, 2022) using the VAR method, which showed that policy interest rates respond positively to unexpected GDP changes. Previous studies have suggested that monetary policy plays a crucial role in regulating economic growth, inflation, and exchange rates (Nyumuah, 2018); (Abbasinejad et al, 2018); (Sethi et al, 2019); (Mandel et al, 2019) (Arintoko, 2021); (Tai Nguyen et al, 2022). (Kim & Lim, 2018) and (Kim et al, 2020) note that monetary policy shocks can affect exchange rates.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Various structural shocks that drive high inflation such as inflation shocks, output shocks, and exchange rate shocks are of greater concern to the central bank In many studies, monetary policy has an impact that includes the impact on output, inflation, and exchange rates. This empirical evidence is provided in studies conducted by, among others, Nyumuah (2018), Abbasinejad et al (2018), Sethi et al (2019), Mandel et al (2019), and Tai Nguyen et al (2022). The results of a study by Arintoko (2021) imply the important role of monetary policy in stabilizing output and inflation in the short run and stabilizing inflation in the long run.…”
Section: Introductionmentioning
confidence: 89%
“…The decisive role of the monetary policy of central banks in ensuring the regulation of inflation has been repeatedly proven by international researchers (Nguyen et al, 2022;Suhendra & Anwar, 2022). In particular, the importance of anti-inflationary policies in ensuring financial stability and macroeconomic growth has been established (Kerimov et al, 2023b).…”
Section: Literature Reviewmentioning
confidence: 99%